Nonlinear Dynamics Numerical Analysis of Rolling Bearing-rotor System based on Finite Element Modeling - Yunlong Li (Jixie chuandong)
Based on the bearing dynamics and rotor dynamics，considering the nonlinear factors such as Hertz elastic contact force and radial clearance between rolling element and inner and outer raceway of rolling bearing. According to Timoshenko beam-axis theory，the finite element discretization model of the bearing-rotor system is established and the Newmark numerical method is used to solve the problem. Meanwhile the nonlinear dynamic behaviors of the system are illustrated by means of bifurcation diagrams，Poincaré maps，frequency spectrum diagrams，phase diagrams and orbit plots. The results shows that，the rotor system presents periodic and aperiodic (quasi periodic or chaos) responses. After passing through the chaotic region，the rotor system enters into chaos through period doubling bifurcation，and then leaves chaos through paroxysmal bifurcation. Reasonable selection of rotor speed and clearance can reduce the non periodic vibration caused by nonlinear bearing force，which can improve the stability of the system. The analytic results will provide a referenced gist for the dynamic stability of dual-rotor-rolling-bearing by the quantitative and qualitative analysis.